2023
DOI: 10.1088/1402-4896/acd7b0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of nitrazepam using leaf-like graphitic carbon nitride nanosheets

Abstract: Benzodiazepines like nitrazepam are extensively used, both as prescribed medications and as illicit drug substitutes, and therefore detection is of prime importance. In this work, the electrochemical detection of nitrazepam using a graphitic carbon nitride (g-C3N4) modified electrode was investigated. The nitrogen-rich carbon material i.e., g-C3N4 was easily synthesized by the thermal condensation method using melamine as a precursor. The platinum electrode was modified by synthesized material and its electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…A biosensor is an innovative tool that combines the selectivity of biological identification with the sensitivity of electrochemistry to quickly and sensitively recognise any type of substance. Electrochemical immunoassays have been continually researched and used in a variety of biosensing sectors due to their high sensitivity, affordability, and quantitative assessment capability [25][26][27][28][29][30].…”
Section: An Overview Of Sars-cov-2mentioning
confidence: 99%
“…A biosensor is an innovative tool that combines the selectivity of biological identification with the sensitivity of electrochemistry to quickly and sensitively recognise any type of substance. Electrochemical immunoassays have been continually researched and used in a variety of biosensing sectors due to their high sensitivity, affordability, and quantitative assessment capability [25][26][27][28][29][30].…”
Section: An Overview Of Sars-cov-2mentioning
confidence: 99%
“…Electrochemical biosensors provide distinct advantages in comparison to other analytical techniques due to their capacity to directly convert biological phenomena into electrical signals, hence ensuring exceptional signal stability; for example, Ahmed et al demonstrated the work based on an inverse opal scaffold integrated with molecularly imprinted polymer (MIP) for the assessment of histamine biomolecule by employing the electrochemical approach. Furthermore, the electrochemical method is considered to be a more favorable approach in comparison to other analytical methods due to its ability to offer improved sensitivity, selectivity, cost-effectiveness, real-time monitoring, compatibility with complex matrices, versatility, and rapid operation. This is particularly advantageous, as it eliminates the need for a highly skilled operator and expensive equipment that is typically required by alternative methods. For example, the electrochemical sensor developed by Jiménez et al was designed to detect capsaicin in real-life specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials are substances with a thickness of just one or two atoms. , These materials possess distinctive and noteworthy electrical, optical, thermal, and mechanical characteristics as a result of their decreased dimensionality. Graphene is a 2D material composed of a single layer of carbon atoms organized in a hexagonal architectural lattice. , Nevertheless, other alternative 2D materials have garnered interest due to their unique characteristics and their uses.…”
Section: Introductionmentioning
confidence: 99%